Who will take over the libraries of the New Europe? - Hollender, Henryk (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
When we take a look on any map, we see that the 2004 and 2007 enlargements of the European Union can’t help but have a tremendous impact on the future of the continent. It cannot go unnoticed that the shape of the continent has substantially changed; even of we do not know that the total surface of the EU countries is now 4,324,782 km² (or 1,669,807 sq mi) as opposed to over 3,250,000 km² at the break of the Millennium. The population, nearly half a billion, has risen by 21%, and it includes large countries, like Poland, which itself makes 8% of the EU population. Here is New Europe, or NE. Having admitted Bulgaria, Cyprus, the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Malta, Poland, Romania, Slovakia and Slovenia, the European Union, apart from the ideas behind it, its politics and its government, can never be the same.